Therapeutic Drug Monitoring of Asparaginase: Intra-individual Variability and Predictivity in Children With Acute Lymphoblastic Leukemia Treated With PEG-Asparaginase in the AIEOP-BFM Acute Lymphoblastic Leukemia 2009 Study. Issue 3 (June 2020) - Würthwein, Gudrun; Lanvers-Kaminsky, Claudia; Gerss, Joachim; Möricke, Anja; Zimmermann, Martin; Stary, Jan; Smisek, Petr; Attarbaschi, Andishe; Nath, Christa; Zucchetti, Massimo; Rizzari, Carmelo; Schrappe, Martin; et al.
Abstract : Background: Therapeutic drug monitoring (TDM) can identify patients with subtherapeutic asparaginase (ASNase) activity [silent inactivation (SI)] and prospectively guide therapeutic adaptation. However, limited intra-individual variability is a precondition for targeted dosing and the diagnosis of SI. Methods: In the AIEOP-BFM acute lymphoblastic leukemia (ALL) 2009 trial, 2771 children with ALL were included and underwent ASNase-TDM in a central laboratory in Münster. Two biweekly administrations of pegylated ASNase during induction and a third dose during reinduction or the high-risk block, which was administered several weeks later, were monitored. We calculated (1) the incidence of SI; and (2) the predictivity of SI for SI after the subsequent administration. ASNase activities monitored during induction were categorized into percentiles at the respective sampling time points. These percentiles were used to calculate the intra-individual range of percentiles as a surrogate for intrapatient variability and to evaluate the predictivity of ASNase activity for the subsequent administration. Results: The overall incidence of SI was low (4.9%). The positive predictive value of SI identified by one sample was ⩽21%. Confirmation of SI by a second sample indicated a high positive predictive value of 100% for biweekly administrations, but not for administration more than 17 weeks later. Sampling and/or documentation errors were risks for misdiagnosis of SI. High intra-individual variability in ASNase activities, with ranges of percentiles over more than 2 quartiles and low predictivity, was observed in approximately 25% of the patients. These patients were likely to fail dose individualization based on TDM data. Conclusions: To use TDM as a basis for clinical decisions, standardized clinical procedures are required and high intra-individual variability should be taken into account. Details of the treatment are available in the European Clinical Trials Database at https://www.clinicaltrialsregister.eu/ctr-search/trial/2007-004270-43/DE . Abstract : Supplemental Digital Content is Available in the Text.